Penentuan Sistem Pusat Pelayanan Perkotaan Berdasarkan Data Point of Interest di Kota Pangkalpinang - Hadi Fitriansyah; Dwi Rizka Zulkia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
An interconnected city service system exists in urban areas. A good urban space structure should be able to encourage sustainable development for the people and the countryside, as a process of changing the use of dynamic urban space. The high service requirements of the central area of Pangkalpinang City are not offset by the availability of adequate urban facilities. The purpose of this study is to describe the service center system in Pangkalpinang City. The method used in this research with kernel density analysis uses POI (Point of Interest) data related to social, cultural, economic, and/or public administration. Analysis results showed that the Padi Market Area is still a potential service center in Pangkalpinang City, with the main character of trade and services. This is in line with the 2011-2030 RTRW of Pangkalpinan City that makes the Pedi Market area the service center of Pangcalpinang Town. Several areas have the potential to develop functions and roles as a City Service Subcenter. The results of this analysis are expected to provide recommendations to policymakers in drawing up the structure of urban spaces in urban spatial documents.